Effect of Variation of Moringa Leaf Extract (Moringa oleifera L.) on Antioxidant Activity of Edible Film CMC/Chitosan - Rezky A. Zainuddin; Basuki Wirjosentono; Cut F. Zuhra (Universitas Tadulako, 2022)
The edible film is an alternative to using synthetic polymer products because it is non-toxic, biodegradable, increases food safety, and extends food shelf life. The purpose of this study was to see how the effect of adding Moringa leaf extract on the antioxidant activity of CMC/Chitosan edible film. This study consisted of two stages, the first stage was extracting Moringa leaves using ethanol, and the second stage was making edible film CMC/chitosan with the addition of variations of Moringa leaf extract (0.5%, 1%, 1.5%, and 2%). The results of the antioxidant activity test showed that the edible film with the best variation was EE with an IC50 value of 4.45 ppm which was categorized as very strong and physical properties such as absorption, solubility, and water vapor transmission were 72.19%, 92.04%, and 6.21 g/m2h.